A comprehensive study on the relationship between mechanical properties and microstructural development of calcium sulfoaluminate cement based self-leveling underlayments. (28th February 2018) - Xu, Linglin; Li, Nan; Wang, Ru; Wang, Peiming
Highlights: Both mechanical properties and hydration of CSA based SLU was evaluated. The formation of hemicarbonate was hindered by the addition of anhydrite. Ettringite formed at different hydration stage plays different roles on properties. Abstract: In this study, the mechanical properties of calcium sulfoaluminate cement based self-leveling underlayments (SLU) prepared with various amount of anhydrite were evaluated through setting times, flowability, compressive strengths and linear shrinkage tests. Meanwhile, to optimize the workability and cost, a high percent of limestone powder was added in all the blends. Influences of CSA cement clinker variety and anhydrite dosage on the hydration of SUL were investigated in terms of the phase assemblage and microstructural development between 1 h and 56 d. Results show that the main hydrates of the control SUL samples made with neat CSA cement clinker and limestone powder are hemicarbonate, monosulfate, aluminium hydroxide and minor amounts of ettringite; massive ettringite and aluminium hydroxide are observed once anhydrite is further added. The SLU containing neat CSA1 cement clinker exhibits higher compressive strengths and drying shrinkage compared with those of neat CSA2 cement clinker. But such differences among different CSA cement clinkers based SLU are getting narrower with increasing anhydrite dosage. Those SLU samples made with 30% anhydrite yield the highest strength but the lowest drying shrinkage. The formation of ettringite at early term mainly contributes to strength development, while the formation of ettringite at later hydration stage favors to decrease the late-term drying shrinkage.